QOLP-14. PRELIMINARY EXAMINATION OF CONFIRMED GLIOMA RISK FACTORS AMONG EPENDYMOMA PATIENTS IN THE NEURO-ONCOLOGY BRANCH NATURAL HISTORY STUDY (NOB-NHS) AND RISK AND OUTCOMES STUDY (ROS). (5th November 2018) - Acquaye, Alvina; Armstrong, Terri; Vera, Elizabeth; Crandon, Sonja; Fletcher Ruiz, María; Aboud, Orwa; Boris, Lisa; Brown, Miranda; Garren, Nancy; Ji, Ming; Levine, Jason; Romo, Carlos; et al.
Abstract: BACKGROUND: The Glioma International Case-Control (GICC) study is the largest study to date examining genetic and environmental risk factors for adult gliomas. Inverse associations have been repeatedly confirmed for allergies, atopic skin diseases, and viral infections. Evaluations of these risk factors specifically ependymoma has not been completed, due to the rarity compared to other glioma types. Therefore, the purpose of this report is evaluating the associations of these confirmed glioma risk factors with ependymomas. METHODS: Adult ependymoma patients (n=128) enrolled in the NOB-ROS and NHS completed a risk factor questionnaire adapted from the GICC study via a web-based portal. Survey sections related to history of asthma/allergies, common infectious diseases, and regular antihistamine/anti-inflammatory use were examined. Ependymoma patients exposed to these factors were calculated and compared to control (n=1, 534) and glioma cases (n=1, 339) from a published report (Scheurer, 2011). Odds ratios were calculated for ependymoma using the published controls to compare risk factor effects between ependymoma and glioma cases. RESULTS: The sample was mostly female (62%), median age=45, white (95%), diagnosed with an ependymoma (52%)in the spine (66%). Ependymoma patients were: less likely to have history of asthma/allergy (41%) than controls (66%; OR 0.36, p<0.001); more likely to report regular antihistamine use (23%) than controls (11%; OR 2.38, p<0.001) and all glioma cases combined (p<0.001); and more likely to report regular anti-inflammatory use than all glioma cases combined (p=0.02). CONCLUSION: Asthma/allergy effects may be more pronounced among ependymoma cases compared to gliomas overall. However, effects of antihistamines and NSAIDs are MUCH worse in ependymoma cases compared to published effects in all cases. This is the first report in adult ependymoma patients exploring risk factors reported in other gliomas and provides preliminary understanding of potential differences in ependymomas. Further analysis should be explored to identify significant areas of concern.